Post Trade War Era: Investor Strategies For Dealing With Falling Gold Prices - Selviani; Sintya Gracella; Siti Aisya; Wenni Anggita (Equity: Jurnal Ekonomi, 2026)
This study analyzes the impact of the U.S.–China trade war de-escalation on global gold prices and investor strategies. During 2020–2025, trade tensions drove gold prices upward as a safe-haven asset, yet after the trade agreement in April–May 2025, gold prices declined as market confidence improved and investors shifted to riskier instruments such as stocks and bonds. The research employed a quantitative-descriptive approach using linear regression, event study, and portfolio strategy evaluation based on modern portfolio theory. Data were collected from global gold prices (XAU/USD), volatility indices, the U.S. dollar index, and questionnaires completed by 43 retail investors in Indonesia. The findings show that trade war de-escalation significantly affects gold prices (34.3%) and investor strategies (27.2%). These results highlight the crucial role of geopolitical stability, while other factors such as inflation, monetary policy, and exchange rates also play significant roles. The study recommends portfolio diversification, the application of Dollar-Cost Averaging (DCA), and improved financial literacy to help retail investors adapt to post-trade war market fluctuations.